Diagnostic uncertainty of hepatobiliary cystadenoma: Report of 11 cases and review of the literature. Issue 1 (February 2016) - Al-Qahtani, Hamad H.
الملخص: أهداف البحث: أجري هذا البحث لتسليط الضوء على عدم دقة التشخيص قبل الجراحي للأورام الكيسية الغدية الكبدية الصفراوية، واقتراح استراتيجيات لتحسين إمكانية التشخيص. طرق البحث: تم ضم جميع المرضى المنومين على التوالي الذين لديهم الورم الكيسي الغدي الكبدي الصفراوي في الفترة من يوليو ٢٠٠٧ حتى يوليو ٢٠١٤ في هذه الدراسة. تم مراجعة السجلات الطبية للمرضى المؤهلين من أجل: التركيبة السكانية٬ والمظاهر السريرية٬ والفحوصات المخبرية٬ ونتائج الأشعة٬ والإجراءات الجراحية٬ والخزعة المجمدة، والمضاعفات٬ والتشريح المرضي٬ والمتابعة في العيادات الخارجية ٬ والأمراض والوفيات. النتائج: تم علاج ١١ مريضا تم تشخيصهم بالأورام الكيسية الغدية الكبدية الصفراوية في وحدتنا. أجري لجميع المرضى أشعة صوتية وأشعة مقطعية مسحية للبطن٬ بينما تم عمل تصوير بالرنين المغناطيسي لثلاثة مرضى مشتبه بإصابتهم بالأورام الكيسية الغدية الكبدية الصفراوية. خضع ستة مرضى لجراحة نهائية٬ بينما تم تشخيص خمسة مرضى بالخطأ حيث اعتقد أنه ليس لديهم ورم كيسي غدي كبدي صفراوي (٢ كيس عداري و٣ كيس بسيط)، وذلك وفقا للأشعة الصوتية والأشعة المقطعية المسحية قبل الجراحة. وقد أجري للخمسة مرضى إزالة جراحية لسطح الكيس. كانت الخزعة المجمدة إيجابية لدى اثنين من المرضى وسلبية كاذبة عند واحد منهم وتم تشخيصه بكيس بسيط. بينما أظهر التشريح المرضي النهائي أورام كيسية غدية كبدية صفراوية لدى جميع المرضى. الاستنتاجات: الأورام الكيسية الغدية الكبدية الصفراوية نادرة، وغالبا يتم تشخيصها بالخطأ كأضرار كبدية كيسية ينتج عن ذلك عدم كفاية العلاج الجراحي. إن تشخيص الأورام الغدية الكيسية الكبدية الصفراوية يجب أن يؤخذ في الاعتبار لدى جميع المرضى الذين لديهم أضرارا كبدية كيسية غير معتادة. المزيد من التقييم قبل الجراحة بالتصوير بالرنين المغناطيسي، وإجراء الخزعة المجمدة أثناء العملية يمكن أن يحسن إمكانية التشخيص وبالتالي يوفر فرصة الاستئصال الجذري النهائي. Abstract: Objectives: This research was conducted to highlight the pre-operative diagnostic uncertainty of hepatobiliary cystadenomas and to suggest strategies to improve its diagnostic yield. Methods: All consecutive patients admitted with hepatobiliary cystadenomas from July 2007 to July 2014 were recruited in this study. The following information was retrieved from the medical records of eligible patients: demographics, clinical features, laboratory tests, imaging results, operative procedures, frozen sections, complications, histopathology, outpatient follow-up, and morbidity and mortality. Results: Eleven total patients with a diagnosis of hepatobiliary cystadenomas were treated in our unit. Abdominal ultrasounds and computed tomography (CT) scans were performed in all patients; magnetic resonant imaging (MRI) was performed in three patients with suspicion of hepatobiliary cystadenomas. Six patients underwent a definitive surgery; five patients were incorrectly diagnosed with non-hepatobiliary cystadenoma liver cysts (2 hydatid cysts and 3 simple cysts) by the pre-operative ultrasound and CT scan. These five patients underwent surgical deroofing. The frozen section was positive in two patients and was falsely negative in one patient who was diagnosed with simple cysts. The final histopathology results identified hepatobiliary cystadenomas in all patients. Conclusions: Hepatobiliary cystadenomas are rare and are frequently misdiagnosed as hepatic cystic lesions with resultant inadequate surgical treatments. A diagnosis of hepatobiliary cystadenomas should be considered in all patients with atypical liver cystic lesions. Further pre-operative assessment with MRIs and intra-operative frozen sections may improve the diagnostic yield and provide an opportunity for a definitive radical resection.